2022
DOI: 10.1177/00207314221083871
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Pharmaceutical Industry Funding of Patient Organisations in Nordic Countries: Can Industry Self-Regulation Deliver on its Transparency Promise?

Abstract: Pharmaceutical companies regularly fund patient organizations. It is important for patient organizations’ credibility that there be transparency regarding this financial support. In Europe, the pharmaceutical industry promises to deliver transparency through self-regulation, as opposed to legally binding provisions, but self-regulation's effectiveness is contested. We compared the industry's transparency of funding in four Nordic countries that, given their general reputation for high transparency, offered a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We examined disclosure practices suggested by to-date analyses of self-regulation [ 55 , 115 – 117 ]. First, the availability of disclosures, understood as the share of companies publishing disclosures within companies committing to disclosure rules.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We examined disclosure practices suggested by to-date analyses of self-regulation [ 55 , 115 – 117 ]. First, the availability of disclosures, understood as the share of companies publishing disclosures within companies committing to disclosure rules.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, as such, public regulation not a panacea. Any legislation should be premised on a comprehensive international evaluation of disclosure rules , practices and data [ 24 , 46 , 55 , 175 ], including their unintended consequences [ 23 , 176 , 177 ]. One structured way of embedding the perspectives of HCPs, HCOs, patients, and members of the public into the policy proposals would involve developing a “theory of change” [ 178 ] capturing multifaceted relationships between disclosure, transparency, as well as the economic power of the industry and the state’s regulatory power [ 18 20 ].…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these firms should be more likely to employ lobbying as the benefit can be disproportionally larger. It was found that lobbying helps pharmaceutical companies to expand access to novel drugs, instead of lowering prices which is clearly beneficial to consumers (Pashley et al, 2022). In addition, these firms tend to possess greater innovative capabilities and focus on products that are more novel in the current market.…”
Section: Hypothesis Developmentmentioning
confidence: 99%